THEORETICAL AND LEGAL BASIS OF CLASS ACTION LAWSUITS IN COMMERCIAL PROCEEDING - Козирєва, Валентина Петрівна; Гаврилішин, Анатолій Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article deals with theoretical and legal issues of a class action lawsuit in commercial-legal proceedings on the basis of the analysis of the norms of the current legislation and scientific views of domestic scientists. Methods: the research has been conducted using the classical methods of scientific knowledge. Using the method of the analysis, system elements of a legal mechanism of class action lawsuits have been disclosed. With the help of the comparative method, the institute of procedural multiplicity and class action lawsuits in foreign countries have been considered. Results: the author’s definition of a concept of a class action lawsuit in the commercial proceeding has been formulated. The components of the origin (preconditions) of the right on a class action lawsuit have been determined and disclosed. Discussion: of the problem of applying class action lawsuits in the commercial proceeding and the need for its introduction into the Commercial Proceeding Code.